Respuestas
Respuesta dada por:
2
Respuesta:
Explicación paso a paso:
x = 2y - 7
x + y = 20 Reemplazando "x"
2y-7+y=20
3y=20+7
3y=27
y=27/3
y=9
x = 2y - 7 Reemplazando "y"
x=2(9)-7
x=18-7
x=12
Respuesta dada por:
2
Respuesta:
El valor de x es 11 y el valor de y es 9
Explicación paso a paso:
x + y = 20
x = 2y - 7
x + y = 20 +
- x + 2y = 7
0 + 3y = 27
3y = 27
y = 27/3
y = 9
Reemplazamos:
y = 9
x + y = 20
x + 9 = 20
x = 20 - 9
x = 11
Espero que te sirva de algo
ATTE: 616Moloch616
Preguntas similares
hace 5 años
hace 5 años
hace 8 años
hace 8 años
hace 9 años
hace 9 años